Contribution of Icelandic ice caps to sea level rise: Trends and variability since the Little Ice Age. Issue 8 (29th April 2013) - Björnsson, Helgi; Pálsson, Finnur; Gudmundsson, Sverrir; Magnússon, Eyjólfur; Adalgeirsdóttir, Gudfinna; Jóhannesson, Tómas; Berthier, Etienne; Sigurdsson, Oddur; Thorsteinsson, Thorsteinn
Abstract : [1] In total, Icelandic ice caps contain ∼3600 km 3 of ice, which if melted would raise sea level by ∼1 cm. Here, we present an overview of mass changes of Icelandic ice masses since the end of the 19th century. They have both gained and lost mass during this period. Changes in ice volume have been estimated both through surface mass balance measurements (performed annually since ∼1990) and differencing of digital elevation models derived from various satellite and airborne observations. While the glaciers showed little mass loss as the 20th century began, losses increased rapidly after 1925, peaked in the 1930s and 1940s, and remained significant until the 1960s. After being near‐zero or even positive during the 1980s and early 1990s, glacier mass budgets declined considerably, and have since the mid‐1990s shown an average annual loss of 9.5±1.5 Gt a −1, contributing ∼0.03 mm a −1 to sea level rise. Since 1995 interannual variability in mass loss is high, ranging from 2.7 to 25.3±1.5 Gt a −1, corresponding to surface mass balances of −0.2 to −2.2 ± 0.15 mwe a −1 . This variability is driven by climate fluctuations and also by transient reduction of albedo due to volcanic eruptions. Key Points: Icelandic ice caps both gained and lost mass since end of the 19th century mass variability driven by climate and temporary volcanic events mass balance variations relate to air temperature rather than precipitation